Synthesis, Characterization and Antimicrobial properties of Oxovanadium(IV) Complexes Derived from Schiff Base Ligand Containing Thiosemicarbazone Moiety - VERMA, PARUL; KUMAR, SHALIN; DHAR, D.N. (Asian Journal of Chemistry, 2010)
The synthesis and characterization of the complexes of oxovanadium(IV) is reported here-in of [VOL1(H2O)2]SO4 (L1 = Schiff bases ligands containing thiosemicarbazone moiety) i.e., bis(p-methxoybenzaldehyde) thiosemicarbazone, bis(N,N′-dimethyl-4-aminocinnamaldehyde) thiosemicarbazone, bis(pyridine-2-aldehyde) thiosemicarbazone, bis(pchlorobenzaldehyde) thiosemicarbazone, bis(indole-3-aldehyde) thiosemicarbazone, bis(3-methylsalicylaldehyde)thiosemicarbazone, bis(5-methylsalicylaldehyde)thiosemicarbazone, bis(furfuryl-2-aldehyde) thiosemicarbazone and bis(5-bromosalicylaldehyde) thiosemicarbazone. All the complexes of characterized by elemental analysis, molar conductivity, magnetic moments, thermal studies, EPR, IR and electronic spectra. These studies show octahedral geometry around the metal ion. These complexes were also screened for their antibacterial and antifungal activities.